Association of age at menarche with valvular heart disease: An analysis based on electronic health record (CREAT2109) - Sun, Zhiyu; Zhu, Yongjie; Sun, Xiaoyan; Lian, Zhexun; Guo, Mengqi; Lu, Xiaohong; Song, Ting; Feng, Luxin; Zhang, Yi; Xu, Yawei; Ji, Hongwei; Guo, Junjie (Frontiers in Cardiovascular Medicine, 2023)
Objective The association between age at menarche and coronary heart disease (CHD) has been reported, but the association between age at menarche and valvular heart disease (VHD) has not been described. We aimed to assess the association of age at menarche with VHD. Methods By collecting data from four medical centers of the Affiliated Hospital of Qingdao University (QUAH) from 2016-01-01 to 2020-12-31, we sampled 106779 inpatients. A case-control study design was used in this study. The main outcome of this study was VHD which was diagnosed based on ICD-10 coding, and the exposure factor was age at menarche which was accessed through the electronic health records. We used Logistic regression model to investigate the association between age at menarche and VHD. Results Compared with women with age at menarche 14-15, the odds ratio of VHD in women with age at menarche ≤ 13,16-17 and ≥18 was 0.71 (95%CI 0.61-0.83), 1.20 (95%CI 1.07-1.34) and 1.27 (95%CI 1.11-1.45), respectively. By restricting cubic splines, we found that later menarche was associated with increased risk of valvular heart disease. Furthermore, after subgroup analysis of different etiologies, the same trend persisted for non-rheumatic valvular heart disease, but no similar association was observed between rheumatic valvular heart disease and age at menarche. Conclusions In this large inpatient sample, later menarche was associated with higher risk of VHD.